The Influence Of Liquidity, Profitability And Capital Structure On Dividend Policy: Empirical Study On The Consumption Goods Industry Sector On The Idx, 2017-2021 - Puspitasari, Ratih; Gunawan, Audreylia; Rachman, Rachmawaty (Institut Bisnis dan Informatika Kesatuan, 2024)
The capital market is one of the tools to make investments, every investor who makes an investment expects a profit from the investment they make. Profit is the main goal when an investor makes an investment, one of the goals of sharing profits that a company can make for its investors to distribute dividends or dividend policy. This study aims to determine whether liquidity, profitability, and capital structure have an influence on dividend policy in consumer goods industry companies in 2017-2021. This study used quantitative methods and purposive sampling techniques to obtain the number of research samples. Based on the purposive sampling technique, it was found that 6 companies had secondary data types that would be used in this study. This research uses multiple linear analysis with SPSS 25.0 application. The research results obtained from this study are that liquidity has no partial effect on dividend policy, profitability has a partial effect on dividend policy, and capital structure has no partial effect on dividend policy. And liquidity, profitability, and capital structure which have a simultaneous influence on dividend policy Keywords: Liquidity, Profitability, Capital Structure, Dividend Policy